Esthesioneuroblastoma - A Case Report - Rao, C. Venkateswara; Prasad, P.R.K.; Chiranjeevi, D. (Indian Journal of Plastic Surgery, 1994)
Esthesioneuroblastoma is an uncommon tumour of the nasal cavity arising from olfactory epithelium. Ever since Berger described the first case of esthesioneuroblastoma in 1924, considerable progress has been made in the diagnosis and management of these tumours. A case report of esthesioneuroblastoma has been presented and relevant literature is reviewed.